MULTI-STAKEHOLDERS GOVERNANCE IN SOCIAL SCIENCE DISCIPLINE: A SYSTEMATIC LITERATURE REVIEW - Taufik, Mohammad; Rahmat, Al Fauzi; Irawan, Bambang; Akbar, Paisal (Natapraja, 2021)
Multi-stakeholders governance (MSG) is a new governance design that involves many experts from multiple stakeholders to participate in dialogue, decision-finding (and possibly decision-making) and solution to common problem that occur. This article aims to analyze and identify topics on multi-stakeholder governance with a focus on social science disciplines. In particular, this article takes qualitative research with a literature study approach. The approach adopted in this paper consists of an initial selection of articles based on keywords of "multi-stakeholder governance" in social science disciplines in the Scopus database - limited to titles, abstracts, keywords, and in English and using articles published from early to 2020. Several stages are then identified; The first stage is analyzing the number of citations and analysis by country, and analysis of cumulative citations. The second stage analyzes the primary approaches, strategies, and scope used in MSG learning. Finally, the primary topic analysis of several previous studies on MSG. Therefore, the study results illustrate that there are eleven main topics in MSG in social science disciplines; some of the propositions on these topics are summarized.